2007
DOI: 10.1007/s12016-007-8003-8
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren’s Syndrome—Study of Autoantigens and Autoantibodies

Abstract: The presence of autoantibodies is the hallmark of systemic autoimmune diseases. During the past 30 years, intense clinical and basic research have dissected the clinical value of autoantibodies in many autoimmune diseases and offered new insights into a better understanding of the molecular and functional properties of the targeted autoantigens. Unraveling the immunologic mechanisms underlying the autoimmune tissue injury, provided useful conclusions on the generation of autoantibodies and the perpetuation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 151 publications
(132 reference statements)
0
81
0
4
Order By: Relevance
“…These Abs are detected in serum and can be produced locally in the affected salivary glands (39). Anti-SSB/La Abs are accompanied by anti-SSA/Ro Abs, whereas anti-SSA/Ro Abs can be found either with or without anti-SSB/La Abs (40). In this study, serum titers of anti-SSA/Ro and anti-SSB/La Abs were evaluated relative to Zp and CYP1A1 promoter activities.…”
Section: The Relationship Between Ahr Activation and Autoantibodies Imentioning
confidence: 99%
“…These Abs are detected in serum and can be produced locally in the affected salivary glands (39). Anti-SSB/La Abs are accompanied by anti-SSA/Ro Abs, whereas anti-SSA/Ro Abs can be found either with or without anti-SSB/La Abs (40). In this study, serum titers of anti-SSA/Ro and anti-SSB/La Abs were evaluated relative to Zp and CYP1A1 promoter activities.…”
Section: The Relationship Between Ahr Activation and Autoantibodies Imentioning
confidence: 99%
“…This is the case since anti-M 3 mAChR IgG binds to, and activates, the mAChR subtype M 3 of the salivary gland. This produces xerostomia and glandular parasympathetic dysfunction, which in the chronic course of the disease, results also in severe extraglandular manifestations [9] [10] [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that anti-Ro/SSA and anti-La/SSB antibodies are directed against ribonucleoprotein complexes [11]. Their localization is mainly cytoplasmic [12] and the increased expression of Ro52 in SS and SLE patients is probably implicated positively or negatively in the alteration of cellular immune responses and in the increased apoptosis observed in pSS patients [13] [14].…”
mentioning
confidence: 99%
“…[16][17][18] The presence of autoantibodies Ro/SSA and La/SSB was found to be generally associated with a longer disease duration, increased frequency of nonexocrine manifestations and a higher intensity of lymphocytic infi ltrates invading the minor salivary glands. 19 Recent case reports and some research have shown that autoantibodies against α-fodrin may be used in the diagnosis and may also be considered as an activation marker of SS with dry eye.…”
Section: Lacrimal Gland Infl Ammationmentioning
confidence: 99%